2018
DOI: 10.13040/ijpsr.0975-8232.9(12).5161-67
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In the present work, a rapid, specific, accurate and precise Reversed phase high performance liquid chromatographic (RP-HPLC) method has been developed and validated for simultaneous determination of Dapagliflozin and Saxagliptin in bulk and pharmaceutical dosage form. Successful chromatographic separation of Dapagliflozin and Saxagliptin was carried out with Inertsil-ODS, C 18 column (250 × 4.6 mm; 5 μm) with mobile phase consisted of a mixture of Methanol and Potassium dihyrogen phosphate buffer in the ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The analytical run duration for the proposed method is short (6 min); hence, this method was rapid and superior than literature methods [8,[11][12][13]. When compared with previous HPLC reports [14][15][16][17][18] for this drug combination, the proposed method has advantages such as high resolution (7.3) and wide linearity range (0.1-150 μg/mL, 0.2-300 μg/mL). Low LOD and LOQ values furnished in the method signify the high sensitivity over literature methods.…”
Section: Methods Comparison With Literature Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The analytical run duration for the proposed method is short (6 min); hence, this method was rapid and superior than literature methods [8,[11][12][13]. When compared with previous HPLC reports [14][15][16][17][18] for this drug combination, the proposed method has advantages such as high resolution (7.3) and wide linearity range (0.1-150 μg/mL, 0.2-300 μg/mL). Low LOD and LOQ values furnished in the method signify the high sensitivity over literature methods.…”
Section: Methods Comparison With Literature Methodsmentioning
confidence: 89%
“…Literature survey revealed that there were few reports published on the simultaneous quantification of dapagliflozin and saxagliptin using UV [8], HPTLC [9], HPLC [10][11][12][13][14][15][16][17][18], and LC-MS [19,20] techniques in bulk drug and pharmaceutical dosage forms. Few methods were reported for analysis of dapagliflozin and saxagliptin separately [21][22][23][24] and in combination with other drugs [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%